PROFITABILITY ANALYSIS FOR MEASUREMENT OF FINANCIAL PERFORMANCE OF MITRA PERDANA SIDOARJO COOPERATIVE - Mardianto, Totok; Siti Khasanaturrohmah (Universitas Teknologi Surabaya, 2024)
This research aims to analyze the financial performance of the Mitra Perdana Sidoarjo Cooperative when viewed from a profitability perspective using the Net Profit Margin Ratio, Benefit to Asset Ratio, Benefit to Capital Ratio for 2020 - 2022. The type of research is Descriptive Qualitative. The research data was obtained from the Mitra Perdana Sidoarjo Cooperative Financial Report for 2020 – 2022. Data analysis is by calculating the profitability ratio using the formula Net Profit Margin Ratio, Benefit to Asset Ratio, and Benefit to Capital Ratio. Financial performance measurement based on KUKM Ministerial Regulation Number 06/Per/M.KUKM/V/2006 The results of the research show that: 1) The financial performance of the Mitra Perdana Sidoarjo Cooperative when viewed from the profitability side using the Net Profit Margin Ratio in 2020, 2021 and 2022 is in an unhealthy condition, 2) The financial performance of the Mitra Perdana Sidoarjo Cooperative when viewed from the profitability side using the Benefit Over Assets Ratio, in 2020, 2021 and 2022 it is in a healthy condition, 3) The financial performance of the Mitra Perdana Sidoarjo Cooperative when viewed from the profitability side using the Benefits Over Capital Ratio, in 2020, 2021 and 2022 is in a healthy condition. The results of this research show that the Net Profit Margin Ratio in 2020 - 2022 has an unhealthy performance, so that the management of the Mitra Perdana Sidoarjo Cooperative in 2020 - 2022 has an unhealthy performance, so that the management of the Mitra Perdana Sidoarjo Cooperative is required to be able to further increase its net profit margin. produced.